BPE-P01: Optimization of media for mass production of Schizophyllum commune using response surface methodology (RSM) - Mohd Kamal, Irnada Syuhaidah; Abdul Halim, Khairul Hazwat; Mohd Nor Rashid, Noraswati; Mel, Maizirwan (2012)
Schizophyllum commune (SC) is an edible mushroom which can be found worldwide except Antactica area. This type of mushroom has attracted attention because of its medicinal important. Optimization of the media composition is required for the higher production of SC mycelium mass in order to meet the demand particularly in pharmaceutical industries. Glucose and yeast extract was selected as carbon and nitrogen sources for the growth of this fungus and were optimised firstly using OFAT (one factor at a time) method. This media composition were then optimized using a response surface methods (RSM) to find the best composition of factors such as inoculum (seed), carbon, nitrogen concentration to produce a maximum mycelium mass as a response. Thirty set of different range medium composition were conducted by RSM design using Design Expert software. The statistical analysis showed that optimum media containing 11.7 % (v/v) of inoculum, 27g glucose and 1.2g yeast extract has given maximum production of mycelium mass where the yields of mycelium mass increased from 6.148g/l (unoptimized) to 15.68g/l in medium (optimized)